2021
DOI: 10.3390/su13105488
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Factors Influencing the Residential Preferences of the Elderly in China

Abstract: The global aging problem has a serious impact on the sustainable development of society. China has become the country with the largest aging population in the world, 1.75 times that of the EU and 3.01 times that of the United States. Therefore, the question of how to develop elderly care services and institutions in China is critical. Based on data from the China Health and Retirement Longitudinal Study (CHARLS), this paper details the residential preferences of the elderly, and uses a multinomial logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Under the influence of traditional ideas, the older adults who need to be cared for are mainly taken care of by their families or relatives, while other services such as public welfare or market-oriented services are only supplementary [ 9 , 10 ]. Although it has always been one of the most important living arrangements for older adults in China to live with children [ 11 ], with the increase of the aging population, empty-nest families, and floating population, most young people are unable to perform filial piety [ 12 ]. According to the seventh population census, China's average household population has less than three for the first time in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of traditional ideas, the older adults who need to be cared for are mainly taken care of by their families or relatives, while other services such as public welfare or market-oriented services are only supplementary [ 9 , 10 ]. Although it has always been one of the most important living arrangements for older adults in China to live with children [ 11 ], with the increase of the aging population, empty-nest families, and floating population, most young people are unable to perform filial piety [ 12 ]. According to the seventh population census, China's average household population has less than three for the first time in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal satisfaction and self-assessed health status of the elderly suggested that the ideal model for designing transition spaces in elderly care facilities is to use semi-open exterior corridors with increasing temperature/humidity from outdoor transition space to an indoor decrease in temperature/humidity. Li et al [21] used a multinomial logistic regression model to analyze the effects of education level, health status, and income level on the residential preferences of the elderly in China. The results show that from a spatial perspective, the residential preference for "living together" tends to be increased from the northeast to the southwest.…”
Section: Introductionmentioning
confidence: 99%
“…As of November 2020, China recorded 264.02 million people aged over 60, accounting for 18.7% of the total population, and 190.64 million people aged over 65, representing 13.5% of the overall population. Care for older people has become a significant issue affecting social development in China ( 1 , 2 ). With a decline in the birth rate and family care functions, community care and home care have failed to provide older people high-quality care services.…”
Section: Introductionmentioning
confidence: 99%